FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH KUNJUNGAN WISATAWAN ASIA FARM SELAMA PANDEMI COVID-19 DI KOTA PEKANBARU - Putri Awaliyah Bamelja; Eriyati Eriyati; Ando Fahda Aulia (Jurnal Economica, 2023)
The purpose of this study was to determine the factors that influence the number of tourist visits to Asia Farm during the COVID-19 pandemic. The population in this study were all visitors to the Asia Farm Pekanbaru tourist attraction as many as 37,538 people. While the sample is 100 people who are determined using the Slovin formula. Data analysis used quantitative descriptive method with multiple linear regression model. The results of data analysis and hypothesis testing can be concluded that health protocols, accessibility and facilities have a positive (+) significant effect on the number of tourist visits to Asia Farm Pekanbaru during the Covid-19 Pandemic. Meanwhile, the ability to manage tourist attractions does not affect the number of tourist visits to Asia Farm Pekanbaru during the Covid-19 Pandemic.